Anterior-Chamber Angle and Axial Length Measurements in Normal Chinese Children. Issue 8 (August 2016) - Jin, Peiyao; Li, Meili; He, Xiangui; Lu, Lina; Zhu, Jianfeng; Chang, Ta Chen; Zou, Haidong
Abstract : Purpose: To establish the physiological distribution of anterior-chamber angle parameters and axial length (AL) in a randomly sampled cohort of Chinese children. Patients and Methods: This was a prospective, cross-sectional study on randomly sampled Chinese children ages 7 to 15 years. Complete ophthalmologic examination was carried out on all participants; anterior-segment parameters and ALs were measured using Fourier-domain optical coherence tomography and automated biometers. Associations between the age, the sex, the refractive error, the iris thickness, the AL, and anterior-chamber depth (ACD) and angle measurements were analyzed using multiple correlation and regression tests. The relationship between the AL and other factors was studied by a linear regression analysis. Only the right eye data were analyzed for statistical purpose. Results: A total of 541 children were enrolled in this study. There were no differences in angle parameters between sexes ( P >0.05), but boys had a longer AL ( P <0.01). The AL increased logarithmically with age in children ( P <0.01, R 2 =0.5552, b =6.18). Although the magnitude of myopia also increased with AL, this association was less robust ( P <0.05, R 2 =0.0917, b =−0.88). A multiple regression test indicated that the age and the ACD were independently associated with the increase in angle width ( b =0.37 to 0.50 and 0.51 to 0.60, respectively; P <0.001). Conclusions: All angle measurements increased with age and were positively correlated with the ACD in children 7 to 15 years of age. The AL increased logarithmically with age.